Metabolomics analysis of the serum metabolic signature of nonalcoholic fatty liver disease combined with prediabetes model rats after the intervention of Lycium barbarum polysaccharides combined with aerobic activity. (29th January 2023) - Fan, Yanna; Zhang, Mengwei; Ma, Jiamin; Zhang, Yannan; Yang, Jianjun
Abstract: Metabolic disorders accompany nonalcoholic fatty liver disease (NAFLD), associated with prediabetes. Lycium barbarum polysaccharides (LBP) seem to be a potential prebiotic, and aerobic exercise has shown protective effects on NAFLD with prediabetes. However, their combined effects on NAFLD and prediabetes remain unclear. This study investigated the effects of LBP and aerobic exercise alone, and their combined effects on the metabolomics of serum, and explored the potential mechanisms utilizing a high‐fat diet‐induced rat model of NAFLD and prediabetes. It provided the metabolic basis for the pathogenesis and early diagnosis of prediabetes complicated with NAFLD. Untargeted metabolomics profiling was performed using ultra‐high‐performance liquid chromatography coupled with quadrupole Orbitrap mass spectrometry to analyze the changes in overall metabolites in each group of samples. An orthogonal partial least squares‐discriminant analysis model with variable importance on projection >1 and p < 0.05 were used as the screening criteria to screen the significant differential metabolites and analyze the expression changes and functional pathways. Different intervention treatments showed clear discrimination by univariate and multivariate analyses. The model group had a high relative level of expression of lipids. Comparison between the two groups showed steroids with high expression after LBP and aerobic exercise treatment separately and alkaloids and fatty acyls with high expression after aerobic exercise and the combination intervention, respectively. Comparison of the five groups showed some of the metabolites to be differently expressed after the intervention improved lipid and fatty acid metabolism. The three types of intervention had sound effects on the changes in liver index for the diseases studied. Furthermore, the combination treatment may be a better choice for disease prevention and treatment than a single treatment. Our analysis of metabolomics confirmed that the different treatments had significant regulatory effects on the metabolic pathways. Our findings strongly support the possibility that aerobic exercise combined with LBP can be regarded as a potential therapeutic method for NAFLD in prediabetics.